Weeding Out the Truth: Adolescents and Cannabis. Issue 2 (March 2016) - Ammerman, Seth; Tau, Gregory
Abstract : The use of cannabis for both legal (similar to alcohol) and medical purposes is becoming more common. Although cannabis remains an illegal Schedule 1 drug federally, as of November 2015, 23 states and the District of Columbia have legalized "medical" cannabis, and 4 states and the District of Columbia have legalized the use of cannabis for adults aged 21 years and older. It is very likely that more and more states will sooner rather than later allow cannabis for both medical and legal purposes. This review article will focus on a variety of issues relevant to the current debate about cannabis, and will address the following: Definitions of cannabis/cannabinoids/related; cannabis delivery methods History of federal legality/illegality of cannabis in the United States Current status of cannabis in the US states: legal medical, decriminalization, legal Use of cannabis medically by adults and adolescents; medical cannabis legalization and impact on adolescent use of recreational cannabis Major medical organizations position statements on cannabis Epidemiology of cannabis use among adolescents Effects and side effects of legal cannabis use; DUI Cannabis use and the adolescent brain DSM-5 Criteria Cannabis Use Disorder and Withdrawal